Utilization of Instagram Social Media as A Means of Marketing In @erigostore - Lulu Hanifah; Harits Hasan Baisa; Naufal Thoriq Akbar; May Dedu (Return : Study of Management, Economic and Bussines, 2024)
This study aims to determine the use of Instagram social media as a means of marketing in @erigostore. By using qualitative research, research data is obtained using document studies where document studies are carried out by reviewing documents related to the research topic. This study used subjects from Erigo Products. The result of this study is that @ErigoStore have excelled at using Instagram as a great marketing tool. They utilize the stage to upload product photos, the grandstand's lifestyle related to their image, hold challenges and prizes, team up with powerhouses, use Instagram highlights like Stories and Reels, and direct their supporters to the site to buy products.